2023
DOI: 10.1093/ecco-jcc/jjac190.0547
|View full text |Cite
|
Sign up to set email alerts
|

P417 Frequent Early Nocebo Complaints but Maintained Clinical Efficacy, Biomarker and Therapeutic drug levels following mandatory Biosimilar Switch in Patients with Inflammatory Bowel disease: Preliminary data from a Prospective Observational Cohort Study

Abstract: Background Current evidence suggests that biosimilar is safe and effective for patients with IBD. There is limited data on and nocebo effect after switching from originator to biosimilar. We aimed to report clinical efficacy, therapeutic drug monitoring, adverse events (AEs), and frequency of nocebo in IBD patients with biosimilar switches. Methods We performed a prospective observational study of 257 consecutive IBD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nocebo effects are psychological, physiological, and neurobiological phenomena associated with actual or perceived harms that occur because of patients' negative expectations, and not due to the known pharmacologic actions of treatment [24][25][26][27]. A prospective observational study reported frequent early nocebo complaints following non-medical biosimilar switch (including infliximab and ADA RP to biosimilar switches) in Canadian patients with inflammatory bowel disease, although biomarker levels and their clinical efficacy were well maintained [28]. Unfortunately, reasons for switching and patient clinical status were unknown in our current study as they were not documented in the LRx claims databases.…”
Section: Patterns Of Switching From Abp 501mentioning
confidence: 99%
“…Nocebo effects are psychological, physiological, and neurobiological phenomena associated with actual or perceived harms that occur because of patients' negative expectations, and not due to the known pharmacologic actions of treatment [24][25][26][27]. A prospective observational study reported frequent early nocebo complaints following non-medical biosimilar switch (including infliximab and ADA RP to biosimilar switches) in Canadian patients with inflammatory bowel disease, although biomarker levels and their clinical efficacy were well maintained [28]. Unfortunately, reasons for switching and patient clinical status were unknown in our current study as they were not documented in the LRx claims databases.…”
Section: Patterns Of Switching From Abp 501mentioning
confidence: 99%